Towards Environmentally Friendly Agriculture: Assisting Farmers in the Use of Organic and Biological Fertilizers - Adi Oksifa Rahma Harti; Rakhmia Nalibratawati; Men Aaf Falahudin; Adi Niko Munandar; Sri Fatmawati (Unram Journal of Community Service, 2025)
Environmentally friendly agriculture is an urgent necessity amid increasing soil degradation and farmers' dependence on chemical fertilizers, which incur high costs and reduce land quality. This condition also occurs in the Hikmah Farmer Group in Majalengka, where the majority of farmers still rely entirely on chemical fertilizers, while knowledge and skills regarding organic and biological fertilizers are still very limited. This Community Service Program (PKM) aims to increase farmers' capacity to produce and utilize organic and biological fertilizers, thereby reducing their dependence on chemical fertilizers and supporting the realization of sustainable agriculture. The implementation methods included counseling on the concept of environmentally friendly agriculture, training in the production of solid and liquid organic fertilizers, as well as biological fertilizers based on local microorganisms, and direct assistance in their application on agricultural land. The results of the activities showed a significant increase in farmers' knowledge and skills, with more than 70% of group members able to produce organic fertilizers independently, and more than 60% successfully applying biological fertilizers on their land. In addition, the use of chemical fertilizers can be reduced by 20-30% without reducing crop yields, while improving soil fertility and increasing soil biota activity. Thus, this program not only has a positive impact on farmers' economic efficiency, but also contributes ecologically to the sustainability of environmentally friendly agriculture. Future recommendations include strengthening institutional support and replicating the program among other farmer groups in Majalengka to ensure its benefits can be sustained and expanded.